Hypothesis about the astronomic function of the underground well temple of Sardinian type in Bulgaria - Tsonev, L.V. (Archaeoastronomy and Ancient Technologies, 2013)
A detailed description is presented of the ancient underground well temple of Sardinian type which was found in Bulgaria in 1971 near the village Garlo. Some interesting peculiarities in the localization and in the construction of the monument are analyzed. Up to now they do not have any satisfactory explanation in the frames of pure archaeology. A new hypothesis of archaeoastronomical and ritual character is proposed here about the function of the temple. The results from preliminary indirect measurements support this hypothesis. For the first time we are able to give a rational explanation of the peculiarities mentioned above. The Gyrlo temple is compared with similar constructions in Sardinia and Crimea.